1994
DOI: 10.1073/pnas.91.3.1163
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation and phosphotransfer in the Bordetella pertussis BvgAS signal transduction cascade.

Abstract: Expression of adhesins, toxins, and other virulence factors of Bordetella pertussis is under control of the BvgA and BvgS proteins, members of a bacterial twocomponent signal transduction family. BvgA bears sequence simlarity to regulator components, whereas BvgS shows similarity to both sensor and regulator components. BvgA and the cytoplasmic portion of BvgS ('BvgS) were overexpressed and purified. 'BvgS autophosphorylated with the vphosphate from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
132
1
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 26 publications
(23 reference statements)
1
132
1
3
Order By: Relevance
“…The N-terminal periplasmic domain of BvgS is involved in signal recognition; via phosphorylation, it transduces the signals into the transcriptional regulation network (Uhl & Miller, 1994). Evidence that BvgS is involved in signalling events is provided by the finding of a class of mutations that make the system insensitive to environmental regulation (Miller et al, 1992;Manetti e t al., 1994;Goyard e t al., 1994).…”
Section: A P R U G N O L a A N D O T H E R Smentioning
confidence: 99%
“…The N-terminal periplasmic domain of BvgS is involved in signal recognition; via phosphorylation, it transduces the signals into the transcriptional regulation network (Uhl & Miller, 1994). Evidence that BvgS is involved in signalling events is provided by the finding of a class of mutations that make the system insensitive to environmental regulation (Miller et al, 1992;Manetti e t al., 1994;Goyard e t al., 1994).…”
Section: A P R U G N O L a A N D O T H E R Smentioning
confidence: 99%
“…In the Evg system of E. coli and the Bvg system of Bordetella pertussis, three signal transduction modules (the transmitter, the receiver and the C-terminal domain containing the HPt motif) are combined in a single protein, the EvgS or BvgS sensory protein, whereas the corresponding effector molecules are typical response regulators (EvgA and BvgA) belonging to the FixJ family with an N-terminal receiver and a C-terminal DNA-binding domain Stibitz and Yang, 1991;Boucher et al, 1994;Uhl and Miller, 1994;Utsumi et al, 1994). Both systems show very significant sequence similarities even outside of the conserved signalling modules and, accordingly, seem to respond to similar external stimuli Utsumi et al, 1994;.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that, similar to the Bacillus and Saccharomyces systems, a complex phosphorelay occurs that involves the autophosphorylation of the BvgS transmitter (His-729) and subsequent phosphorylation of Asp-1023 in its receiver and of His-1172 in its HPt domain before the phosphorylation of BvgA (Uhl and Miller, 1994;1996a). The C-terminal receiver and HPt BvgS domains are essential for signal transduction (Uhl and Miller, 1994;Beier et al, 1995;. The phosphorelay very probably involves dimerization (or oligomerization) of BvgS (Beier et al, 1995;.…”
Section: Introductionmentioning
confidence: 99%
“…BvgS is a 135-kDa sensor protein localized to the cytoplasmic membrane, and BvgA is a 23-kDa cytoplasmic response regulator (4,7,37,49,(50)(51)(52)(53). The signals sensed by BvgAS in vivo are not known, but BvgAS can be inactivated in vitro by growth at a low temperature or by addition of sulfate anion or nicotinic acid to the culture medium.…”
mentioning
confidence: 99%
“…The BvgS periplasmic region has been postulated to sense signals and transmit information to the cytoplasmic domains via the BvgS linker, which lies adjacent to the second transmembrane domain (32). The cytoplasmic portion of BvgS effects the enzymatic steps of signal transduction and can autophosphorylate in vitro with the ␥-phosphate from ATP and transfer a phosphoryl group to BvgA (53,54). BvgA contains an N-terminal receiver domain and a C-terminal helix-turn-helix DNA binding motif (4), and phosphorylation of BvgA has been shown to increase its affinity for specific target sequences (7).…”
mentioning
confidence: 99%